2021
DOI: 10.1080/19585969.2022.2043128
|View full text |Cite
|
Sign up to set email alerts
|

Graph theory in paediatric epilepsy: A systematic review

Abstract: Graph theoretical studies have been designed to investigate network topologies during life. Network science and graph theory methods may contribute to a better understanding of brain function, both normal and abnormal, throughout developmental stages. The degree to which childhood epilepsies exert a significant effect on brain network organisation and cognition remains unclear. The hypothesis suggests that the formation of abnormal networks associated with epileptogenesis early in life causes a disruption in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…In graph theory, the mean clustering coe cient is de ned as a factor that evaluates how well the connection between neighboring nodes around a node is. (20,21) If the mean clustering coe cient value is high, it means that the connectivity between neighboring nodes is high, suggesting that the segregation of the brain network is high. This suggests that the e ciency of information exchanges in the brain network is high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In graph theory, the mean clustering coe cient is de ned as a factor that evaluates how well the connection between neighboring nodes around a node is. (20,21) If the mean clustering coe cient value is high, it means that the connectivity between neighboring nodes is high, suggesting that the segregation of the brain network is high. This suggests that the e ciency of information exchanges in the brain network is high.…”
Section: Discussionmentioning
confidence: 99%
“…Graph theoretical analysis can quantitatively investigate the e cacy of brain network. (20,21) In this study, we observed changes in functional brain connectivity in patients with ESRD undergoing hemodialysis using graph theory and fNIRS. Furthermore, signi cant changes in the mean clustering coe cient, transitivity, and assortative coe cient were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent of integration indicates the ease with which brain regions communicate, which is typically measures in terms of global efficiency [ 18 ]. The belief that seizures are the result of an imbalance between inhibitory and excitatory signals in brain connectivity has prompted many researchers to explore the role of functional connectivity in seizures [ 20 , 21 , 22 , 23 ]. One study using EEG to study fronto-temporal focal epilepsy reported increased functional connectivity (local segregation as well as global integration) in the affected hemisphere [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Falsaperla et al. ( 2021 ) from Catalania in their systematic review identify the utility of graph theory in aiding the diagnosis of paediatric epilepsy, which has significant clinical implications. Pathological social withdrawal termed ‘Hikikomori’ was originally described in Japan but has since been reported in other countries including non-Asian countries.…”
mentioning
confidence: 99%